Digital Era Marketing Strategy Analysis Of Syariah Banking In Indonesia, Study On E-Word-Of-Mouth Relation To Purchase Intention Through Brand Image To Increase Syariah Banking Market Share In Indonesia - Haris Kadarisman; Kholil; Nafiah Ariyani (Jurnal Sains Terapan Pariwisata, 2018)
The digital era offers many opportunities as well as threats, so every organization must analyze it carefully to improve the company's performance. The purpose of this research is to know E-Word-of-Mouth relationship to Purchase Intention to be used as marketing strategy of syariah banking in Indonesia so as to increase market share of Syariah Banking in Indonesia. Method used in this research are e-word-ofmouth variable from Hennig-Thurau et al., (2004), brand image variable from Tjokroaminoto and Kunto (2014), and variable purchase intension from Samuel and Wijaya (2008). The data retrieval technique for this research was done by distributing questionnaires (Area Jabodetabek) directly to the respondents who have been collected and also via email for those who cannot directly give their opinion (gathering in one room). Data analysis method used is test of validity and reliability, descriptive statistic test, seen from mean, median value and gra- ph, from some research variable above and inferential test to test hypothesis through data processing LISREL. The results of the study of 200 respondents showed that; e-word-ofmouth affects brand image, e-word-of-mouth affects purchase intention, brand image has an effect on purchase intention, research result indicates that e-word-of-mouth, brand image has influence to purchase intention , the results of the test obtained show consistent results or in accordance with the findings and theories of some previous studies conducted by M. Jalilvand & Samiei (2012), and Zhang, R. & Tran, T. (2009).